Reseña histórica de las noches venecianas del cantón Vinces como valoración cultural - Arevalo Rodriguez, Daniela Germania (2021)
This case study emphasizes the Historical Review of Venetian Nights as a cultural valuation in the Vinces canton belonging to the Province of Los Ríos, a corner of Ecuadorian geography, bucolic yesterday, today vigorous and aggressive in the achievement of its development, It has arrived gracefully and triumphantly, with many merits and sufficient values, that it has several tourist attractions, makes national or foreign visitors appreciate the different places that this beautiful canton has. This project covers the techniques applied to obtain the information of this historical event, it was the same survey that helped to detect the ignorance that locals and strangers have about the cultural event, it was the descriptive, explanatory and analytical methods that will allow to obtain better results in data collection. In order to increase the tourist, cultural and economic development of the cantón. This idea was taken from a visit that Dr. Nicolás Llaguno Ruiz made to the city of Xochimilco México and wanted to recreate it, Vinces has an extensive and mighty river where water sports such as outboard motor competitions (outboarding) and In canoe. The Ecuadorian economy has always had the distinctive mark of what to do Vinceño, the gold seed generated wealth, favorable culture, contributed to the treasury and in short I cooperate with the national advance, the productive activity of Vinceño was present in the export of bananas, with significant values.